Speech Functions Realized by the First Speakers of an English Debate Competition - Indriyati Hadiningrum (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
Debate is a form of argument or discussion of a particular issue and it usually involves two or more speakers who express different views from each other. In a debate, speakers produce meaningful string of words to express their opinions and the words they produce may contain speech functions. The focus of this study is the speech functions realized by the first speakers in a debate competition. The debate being studied refers to a competition called Indonesian Varsity English Debate (IVED), a national debate competition held in Universitas Jenderal Soedirman. The objectives of this study are to find out the speech function choices realized by both the first speakers of the affirmative and the negative teams; and to see how the use of speech functions contributes to the development of argumentation in the debate. The data was taken from an English debate competition, i.e. the final round of IVED, which was recorded on a video compact disk. The qualitative method was conducted, and the speech functions were categorized based on the network of speech function developed by Suzanne Eggins and Diana Slade (1997). The results of this study show that the speech functions realized by the first speaker of the affirmative team are opening and continuing speech functions. The speakers of the negative team, by contrast, realized opening, continuing, and reacting speech functions because they needed to issue rebuttals of the affirmative arguments.